2013
DOI: 10.1371/journal.pone.0074724
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase T1, O1 and O2 Polymorphisms Are Associated with Survival in Muscle Invasive Bladder Cancer Patients

Abstract: ObjectiveTo examine the association of six glutathione transferase (GST) gene polymorphisms (GSTT1, GSTP1/rs1695, GSTO1/rs4925, GSTO2/rs156697, GSTM1, GSTA1/rs3957357) with the survival of patients with muscle invasive bladder cancer and the genotype modifying effect on chemotherapy.Patients and MethodsA total of 105 patients with muscle invasive bladder cancer were included in the study. The follow-up lasted 5 years. The effect of GSTs polymorphisms on predicting mortality was analyzed by the Cox proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
1
16
0
4
Order By: Relevance
“…Many previous epidemiological studies have reported that GSTs may affect the efficacy of chemotherapy on cancer (Djukic et al, 2013;Duggan et al, 2013;Oliveira et al, 2014;Kap et al, 2014;Goričar et al, 2015). Djukic et al (2013) reported that the GSTT1 active genotype was associated with the prognosis of patients with muscle invasive bladder cancer in a Serbian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous epidemiological studies have reported that GSTs may affect the efficacy of chemotherapy on cancer (Djukic et al, 2013;Duggan et al, 2013;Oliveira et al, 2014;Kap et al, 2014;Goričar et al, 2015). Djukic et al (2013) reported that the GSTT1 active genotype was associated with the prognosis of patients with muscle invasive bladder cancer in a Serbian population.…”
Section: Discussionmentioning
confidence: 99%
“…Djukic et al (2013) reported that the GSTT1 active genotype was associated with the prognosis of patients with muscle invasive bladder cancer in a Serbian population. Duggan et al (2013) conducted a study in an American population with breast cancer and found that the GSTP1 IIe105Val gene polymorphism increased the risk of all-cause mortality in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have investigated the role of GSTM1, GSTT1, and GSTP1 polymorphisms in the susceptibility to chemotherapeutic agent toxicity and have shown that individuals carrying GST variant genotypes are less able to detoxify the metabolites of drugs and carcinogens used for treating colorectal cancer, bladder cancer, osteosarcoma, and breast cancer, among others Djukic et al, 2013;Duggan et al, 2013;Vreuls et al, 2013;Kap et al, 2014). Kap et al (2014) conducted a study involving 755 patients with colorectal cancer and found that GSTM1 might be a predictive marker for the success of oxaliplatin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Kap et al (2014) conducted a study involving 755 patients with colorectal cancer and found that GSTM1 might be a predictive marker for the success of oxaliplatin therapy. Djukic et al (2013) conducted a study with 105 patients with muscle invasive bladder cancer and reported that the GSTT1 active genotypes might have a prognostic role for treatments. Zhang et al (2012) reported the predictive value of GST gene polymorphisms for the prognosis of osteosarcoma patients receiving chemotherapy; the results showed that the GSTP1 gene polymorphism might have an important role in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of GSTO1-1 is associated with the onset of drug resistance in HeLa cells, as well as in protection against cisplatin-induced apoptosis. Resistance of these tumors to therapy protocols containing cisplatin [7] is a frequent problem in clinical practice. This is probably due to activation of survival pathways (Akt and ERK1/2) and inhibition of apoptotic pathways (JNK1) [8].…”
Section: Introductionmentioning
confidence: 99%